2006
DOI: 10.1016/j.ygeno.2006.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the gene encoding the low-density lipoprotein receptor LRP4 cause abnormal limb development in the mouse

Abstract: Positional cloning of two recessive mutations of the mouse that cause polysyndactyly (dan and mdig-Chr 2) confirmed that the gene encoding MEGF7/LRP4, a member of the low-density lipoprotein receptor family, plays an essential role in the process of digit differentiation. Pathologies observed in the mutant mice provide insight into understanding the function(s) of LRP4 as a negative regulator of the Wnt-beta-catenin signaling pathway and may help identify the genetic basis for common human disorders with simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 16 publications
5
67
0
2
Order By: Relevance
“…Lrp4 null mutations in mice result in limb development defects and in perinatal death due to a lack of neuromuscular junction formation (50). Animals with partial loss-of-function mutations (hypomorphic) are viable and present with different degrees of polysyndactyly (41,49). A recent study identified a role of Lrp4 in bone metabolism based on a mouse model harboring a stop , resulting in a R1170W substitution.…”
Section: Discussionmentioning
confidence: 99%
“…Lrp4 null mutations in mice result in limb development defects and in perinatal death due to a lack of neuromuscular junction formation (50). Animals with partial loss-of-function mutations (hypomorphic) are viable and present with different degrees of polysyndactyly (41,49). A recent study identified a role of Lrp4 in bone metabolism based on a mouse model harboring a stop , resulting in a R1170W substitution.…”
Section: Discussionmentioning
confidence: 99%
“…Severe syndactyly and/or oligodactyly are common to all known Lrp4 mutant models and are attributed to disruption in AER patterning (Li et al, 2010;Pohlkamp et al, 2015;Simon-Chazottes et al, 2006;Weatherbee et al, 2006). Similarly, Lrp4 ΔICD/ΔICD mice display severe defects in distal limbs (Fig.…”
Section: Lrp4mentioning
confidence: 96%
“…TopGal, Lrp4 mitt , Lrp4 mte , Lrp4 mdig , Lrp4 ECD , Wise-null, Lrp5-null, Lrp6-null, K14-tTA and tetO-Wise mice were described previously (Ahn et al, 2013;DasGupta and Fuchs, 1999;Johnson et al, 2005;Kato et al, 2002;Pinson et al, 2000;Simon-Chazottes et al, 2006;Weatherbee et al, 2006) (Table S1). All experiments involving mice were performed under approved protocols issued to R.K. as the principal investigator by the Institutional Animal Care and Use Committee of the Stowers Institute for Medical Research (Protocol ID: 2016-0164).…”
Section: Mouse Strainsmentioning
confidence: 99%
“…Because Dkk1 is a negative regulator of WNT signaling that has a very dynamic domain of expression including the AER, the double ridge phenotype has been associated with enhanced canonical WNT signaling. In this regard, reduced or complete loss of Lrp4 (Johnson et al, 2005;Simon-Chazottes et al, 2006;Weatherbee et al, 2006), which also results in excessive canonical WNT signaling (Johnson et al, 2005;Weatherbee et al, 2006), produces phenotypes that are very similar to Dkk1 mutants. Furthermore, the Dkk1 phenotype was corrected by reduced expression of Lrp6 receptor (MacDonald et al, 2004).…”
Section: Altered Aer Morphologiesmentioning
confidence: 99%